The Influence of Social Crowding on Consumers’ Preference for Green Products - Wenting, Feng; Lijia, Wang; Cuixin, Gao (Frontiers in Psychology, 2022)
With the increasingly crowded shopping environment, social crowding has become an important factor that affects consumers' psychology and behavior. However, the impact of social crowding on consumers' preference for green products hasn't been focused. Therefore, the aim of this paper is to empirically investigate the influence of social crowding on consumers' preference for green products. With four studies, the present research examines how social crowding influence consumers' preference and uncovers the underlying psychological mechanism. The research shows that consumers prefer green products more under the condition of high social crowding than low, and safety needs mediate the impact of social crowding on green products preference. However, the impact of social crowding on the preference for products is only significant in green products. It also demonstrates the moderating effect of introversion-extraversion personality traits between social crowding and green products preference. For extraverted consumers, social crowding won't affect their preference for green products, while for introverted consumers, social crowding is more likely to increase their preference for green products. This study contributes to marketing research by proposing and testing a new mechanism underlie social crowding.